Esquemas imagéticos e o domínio de contêiner no uso da estrutura em+a/o(s) em produções escritas de surdos aprendizes de português como língua estrangeira - Schimulfening, Peterson Lima (2018)
In this study, we analyze the use of the structure em+a/o(s) in written productions of deaf leaners of Portuguese as a foreign language. The analysis starts from concepts of Cognitive Linguistics, especially the theory of image schemas (JOHNSON, 1987; LAKOFF, 1987) and the work on categorization, developed by Rosch (1975; 1978). We aimed to verify (i) how a deaf person uses the em+a/o(s) structure when using the written Portuguese language, (ii) how the categorization of this structure happens in Portuguese written language of native listeners of this language and of deaf peo-ple, native of LIBRAS, who have acquired written Portuguese Language as a foreign language and (iii) if there is a transfer of LIBRAS to the written Portuguese language of the deaf informers. The contexts in which the em+a/o(s) structure was analyzed originates from the CONTAINER image schema and were divided into two sets: in-sertion - total and partial - and surface - horizontal and vertical-horizontal. The corpus contains written productions from two groups of subjects who are native Brazilians with undergraduate or graduate education level. The first group consisted of ten (10) deaf individuals who have sign language (LIBRAS) as their first language (F1) and the second group consisted of ten (10) listeners whose first language is Brazilian Portuguese. The results reveal that for the deaf, user of Brazilian Sign Language, the construction of statements with the em+a/o(s) structure is done in a different way. That occurs because the statement construction in Brazilian Sign Language shows the non-necessity to use certain grammar elements which have, at first analysis, a minor semantic value, such as articles and prepositions. Thus, LIBRAS finds other means to express what these linguistic elements denote. In addition, the construction of locus space by the user of Sign Language is very important since it is from it that the deaf can deal with the most diverse situations.